Il concetto d'umiltà nel linguaggio di santa Teresa di Gesù Bambino - Ciesielka, Joanna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
This paper deals with the concept of humbleness in St. Theresa of Lisieux on the basis of her texts. Firstly, the author presents the semic analysis of the adjectives and nouns determining human qualities and attitudes. Based on the analysis, the author determines 3 semantic fields: the field of lack, the field of oblivion and the field of inferiority. Then the author aims to present the unique concept of humbleness according to St. Theresa of Lisieux: observing herself as an imperfect being, wishing to remain so, her joy of being imperfect and perceiving it as a source of good.
The concept of humbleness in the language of St. Theresa of Lisieux